Pelatihan Pengelasan dan Pembuatan Alat Penunjang Laboratorium Pengelasan di Sekolah Menengah Kejuruan Negeri Pertambangan Bungku - Setiawan, Angga Tegar; Amiruddin; Wijayanto, Hendi Lilih; Siswanto, Yudi; Putra, Eriek Aristya Pradana; Alfafa, Abduh Malik; Saputra, Aditiyo Tri (Politeknik ATI Padang, 2023)
Higher education has an important role in the Tri Darma, namely participating in truly educating the lives of the nation and state in society. One step is to make humans no longer objects of development but subjects of development. As a development subject, abilities and skills in mastering science and technology are certainly required. The use of welding technology has developed and is widely used and exploited in the wider community, especially in meeting industrial needs. One of the welding methods is Shielded Metal Arc Welding (SMAW), namely welding using an electric arc. The aim of this activity is to increase the welding competency of Bungku Mining Vocational School students by adding special skills in the form of SMAW welding and providing encouragement and assistance so that Bungku Mining Vocational School students are able to provide welding equipment that supports learning in the laboratory. The benefit of this activity is to provide knowledge and train skills in SMAW welding so that it can be used to develop laboratory facilities.